A new method for decision making problems with redundant and incomplete information based on incomplete soft sets: From crisp to fuzzy - Xia, Sisi; Chen, Lin; Liu, Siya; Yang, Haoran (Zielona Góra: Uniwersytet Zielonogórski)
This research is focused on decision-making problems with redundant and incomplete information under a fuzzy environment. Firstly, we present the definition of incomplete fuzzy soft sets and analyze their data structures. Based on that, binary relationships between each pair of objects and the "restricted/relaxed AND" operations in the incomplete fuzzy soft set are discussed. After that, the definition of incomplete fuzzy soft decision systems is proposed.
Keywords: decision-making; soft sets; incomplete fuzzy soft set; incomplete information; redundant information